2018
DOI: 10.1101/gad.316984.118
|View full text |Cite|
|
Sign up to set email alerts
|

TCF3 alternative splicing controlled by hnRNP H/F regulates E-cadherin expression and hESC pluripotency

Abstract: Alternative splicing (AS) plays important roles in embryonic stem cell (ESC) differentiation. In this study, we first identified transcripts that display specific AS patterns in pluripotent human ESCs (hESCs) relative to differentiated cells. One of these encodes T-cell factor 3 (TCF3), a transcription factor that plays important roles in ESC differentiation. AS creates two TCF3 isoforms, E12 and E47, and we identified two related splicing factors, heterogeneous nuclear ribonucleoproteins (hnRNPs) H1 and F (hn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 70 publications
(83 reference statements)
8
76
0
1
Order By: Relevance
“…hnRNPF/H are RNA-binding proteins with relatively well-characterized roles in mRNA splicing (Wang et al, 2012; Wang et al, 2007; Yamazaki et al, 2018), and our RNA-Seq analysis of hnRNPF/H KD cells reveal hundreds of altered splicing events (see Supplemental Figures S7B-C for examples), consistent with previous studies (Yamazaki et al, 2018). How do these changes in RNA splicing - or, alternatively, some unrelated activity of hnRNPF/H - ultimately drive repression of the MERVL program?…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…hnRNPF/H are RNA-binding proteins with relatively well-characterized roles in mRNA splicing (Wang et al, 2012; Wang et al, 2007; Yamazaki et al, 2018), and our RNA-Seq analysis of hnRNPF/H KD cells reveal hundreds of altered splicing events (see Supplemental Figures S7B-C for examples), consistent with previous studies (Yamazaki et al, 2018). How do these changes in RNA splicing - or, alternatively, some unrelated activity of hnRNPF/H - ultimately drive repression of the MERVL program?…”
Section: Discussionsupporting
confidence: 90%
“…Double knockdown of hnRNPF/H resulted in dramatic alterations in expression of several hundred genes ( Figure 5A ), including significant downregulation of developmentally-relevant genes ( Sfrp4 , Otx2 , Dact2 , Spry1/4 , Gbx2 , Notum , Notch4 , Sall1, Fgf15 , Tdgf1 , Inhbb , Ltbp3 , Fgf4 , Pou4f2 , Prdm14 , Lefty2 , Bmp4 , etc.). The misregulation of this wide array of differentiation-associated genes presumably results from the recently-discovered role for hnRNPF/H in alternative splicing of Tcf3, a key transcription factor involved in stem cell maintenance and differentiation (Yamazaki et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For example, hnRNP H1 and hnRNP F control the inclusion of the E12 or E47 exons of TCF3. Interestingly, the inclusion of the exon E47 is associated to cell differentiation, whereas E12 inclusion contributes to the maintenance of pluripotency [42].…”
Section: A Finely Regulated As Network Controls Human Embryonic Stem mentioning
confidence: 99%
“…Based on these results, we concluded that recruitment of a robust transcriptional activator to the hTERT promoter in differentiated fibroblasts led to only mild accumulation of telomerase mRNA.We next sought to explore the impact of post-transcriptional processing on the abundance and stability of hTERT mRNA in ESCs. Specifically, we focused on alternative splicing of pre-mRNA as a regulatory pathway that has been previously shown to control developmentallyregulated genes and pluripotency-associated factors (20)(21)(22)(23)(24)(25). Many hTERT alternative splice variants have been detected in different cell types, including α/β variants that modulate telomerase activity in cancer cells (26-28).…”
mentioning
confidence: 99%